Latent Enhancers Activated by Stimulation in Differentiated Cells - Ostuni, Renato; Piccolo, Viviana; Barozzi, Iros; Polletti, Sara; Termanini, Alberto; Bonifacio, Silvia; Curina, Alessia; Prosperini, Elena; Ghisletti, Serena; Natoli, Gioacchino (Cell, 2013)
According to current models, once the cell has reached terminal differentiation, the enhancer repertoire is completely established and maintained by cooperatively acting lineage-specific transcription factors (TFs). TFs activated by extracellular stimuli operate within this predetermined repertoire, landing close to where master regulators are constitutively bound. Here, we describe latent enhancers, defined as regions of the genome that in terminally differentiated cells are unbound by TFs and lack the histone marks characteristic of enhancers but acquire these features in response to stimulation. Macrophage stimulation caused sequential binding of stimulus-activated and lineage-determining TFs to these regions, enabling deposition of enhancer marks. Once unveiled, many of these enhancers did not return to a latent state when stimulation ceased; instead, they persisted and mediated a faster and stronger response upon restimulation. We suggest that stimulus-specific expansion of the cis-regulatory repertoire provides an epigenomic memory of the exposure to environmental agents. [Display omitted] ► Latent enhancers are regulatory elements unmarked and unbound in differentiated cells ► Stimulus-dependent TFs co-opt lineage-determining TFs to activate latent enhancers ► Latent enhancers may confer short-term memory of environmental exposure ► Environmental stimulation qualitatively alters the pre-existing enhancer repertoire Latent enhancers are activated in fully differentiated cells by extracellular signals and may provide a short term memory of signal exposure.